The dispute surrounding the racial debate in Brazil: theory and method for advancing the critical perspective - Souza, Cristiane Luiza Sabino (Argumentum, 2024)
This paper aims to open a debate on the political and theoretical dispute surrounding the racial debate in Brazil today, as well as to demarcate Marxist critical social theory and its development by Latin American and Caribbean intellectuals as a fundamental basis for advancing the interpretation of the inseparability between race and class, anti-racism and anti-capitalism.